2016
DOI: 10.1016/j.rmed.2016.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Physiological responses during exercise with video games in patients with cystic fibrosis: A systematic review

Abstract: Interactive video games generate a heart rate response similar to the intensity required for training in CF patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 35 publications
4
17
0
1
Order By: Relevance
“…The results of the present review corroborate the findings of a systematic review into the effects of AVGs on people with CF [34], which found the heart rate (HR) response to active video gaming was similar to the traditional methods of physical training. One study included in that review, but which was excluded from the present review (as it didn't compare AVGs to traditional exercise or to rest), found the HR target for moderate physical activity (64% of predicted maximum HR) was met during the boxing activity of the Likewise, the results of the present review are consistent with a meta-analysis of AVGs for healthy adults and children by Peng et al [66], who concluded that the HR, energy expenditure and oxygen consumption were no different between AVGs and traditional physical activities.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The results of the present review corroborate the findings of a systematic review into the effects of AVGs on people with CF [34], which found the heart rate (HR) response to active video gaming was similar to the traditional methods of physical training. One study included in that review, but which was excluded from the present review (as it didn't compare AVGs to traditional exercise or to rest), found the HR target for moderate physical activity (64% of predicted maximum HR) was met during the boxing activity of the Likewise, the results of the present review are consistent with a meta-analysis of AVGs for healthy adults and children by Peng et al [66], who concluded that the HR, energy expenditure and oxygen consumption were no different between AVGs and traditional physical activities.…”
Section: Discussionsupporting
confidence: 86%
“…This review was limited in scope as it only aimed to review the exercise intensity of AVGs for people with CF [34], and therefore only included five studies. Another broad review of video games in rehabilitation did not include respiratory conditions, and instead focused on ageing and pathologies such as stroke and Parkinson's disease for which there was more evidence [35].…”
Section: Introductionmentioning
confidence: 99%
“…Exergaming consoles are relatively inexpensive, with the Nintendo Wii and Microsoft Xbox Kinect currently costing less than £250 and £300, respectively. Recent systematic reviews have demonstrated the feasibility, acceptability and effectiveness of exergaming at improving balance, functionality, cognition and QOL in individuals with chronic conditions, including Parkinson’s disease (PD) [ 24 ], multiple sclerosis (MS) [ 31 ], cystic fibrosis [ 32 ] and those who have recently suffered a stroke [ 33 ]. Exergaming has also been found to be a fun and enjoyable method of physical activity, potentially increasing one’s motivation to partake in exercise programs [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…The potential health effects of these active games on children have been extensively demonstrated [16][17][18][19][20], and these effects include increased energy expenditure, the attainment of moderate PA levels, decreased sedentary time, increased overall muscle strength, and improved cardiopulmonary fitness. In children with CF, studies have reported that AVGs produce high physiological demands similar to conventional exercise programmes [21][22][23]. Likewise, previous studies have shown that participants experience greater enjoyment, lower dyspnoea, and increased muscle performance when using AVGs in comparison to high-intensity cycling [24].…”
Section: Introductionmentioning
confidence: 98%